Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Pengangguran Di Kabupaten Mimika - Abu Bakar; Muhammad Nur Faisal (STIE Jambatan Bulan, 2022)
This study aims to determine the effect of government spending and investment on the unemployment rate in Mimika Regency. The method used in this research is associative research method. To achieve the objectives of this study, the data analysis instrument used was multiple linear regression, using the SPSS program. The data in this study were collected using documentation techniques, which were sourced from the Central Bureau of Statistics of Mimika Regency. The results of this study indicate that government spending has a negative effect on the unemployment rate, while investment has a positive effect on the unemployment rate.